Quality Standards of Vocational High Schools Based on the Level of Community Satisfaction - Marlianti, Yenni (PPSDP International Journal of Education, 2023)
This study aims to evaluate the community satisfaction level in relation to the quality standards of vocational high schools. Quantitative techniques are used in the research process. instruments for gathering data that include surveys, documentation, and literature reviews. Descriptive statistical techniques and percentage formulas are used in data analysis. According to the study’s findings, the community in Kayuagung District is quite satisfied with the quality of the Vocational High School (SMK) based on: (1) expectations for graduates’ abilities after attending SMK; (2) the community’s perspective on the learning process’s quality; (3) community satisfaction with the standards of educators and education staff is based on community knowledge about According to the study’s findings, the community’s level of satisfaction with the quality of vocational high schools (SMK) in the Kayuagung District is still subpar.